For the differentiable function on the interval [1, 3] f(1)=-2 f(2)=4 f(3)=-2 Which of the following must be true? I. There must be at least one point on the interval...

For the differentiable function on the interval [1, 3] f(1)=-2 f(2)=4 f(3)=-2 Which of the following must be true? I. There must be at least one point on the interval...

I am not sure what x should be. I have the (-infinity, infinity) but I am not sure how to get the function.

for the function f(x)=x^3-2x^2-3x, find the values where Rolle's Theorem is true.

Find all functions g : R → R such that for any real numbers x and y g(x + y) + g(x)g(y) = g(xy) + g(x) + g(y).

Difference between function of x and function of 1/x. F(x) and F(1/x)

Why ((x-1)^2)^(1/3)+((x+1)^2)^(1/3) is an even function?

g(n) = 3n + 2 f(n) = 2n2 + 5 find g(f(2))

What is the zeros of The reciprocal of arctanh (x) ? In other words. Does the reciprocal V.asymptotes become zero or not ?

1. Let f(x)=5x and g(x)=x^2+1, when the domain of x is all real numbers. a. Find f^-1(x). b. Find (f ° g)(7).

Given g(x)=3x^2−2x+19, find g(t-1). I am pretty sure the g (t-1) would go in the x's spot, but i am having trouble getting the amswer.

a.) Find the inverse of f(x) and name it g(x). Show and explain your work. b.) Use composition to show that f(x) and g(x) are inverses of each other

A worker gets 18 dollars per hour for a normal work week of 40 hours and time-and-a-half for overtime. Assuming he works at least 40 hours a week, construct a function describing his weekly paycheck,...

find the inverse of the function y=8x2 which has an inverse of y-1

find the inverse of the function y=6x2 which has an inverse of y-1

given the function P(x)=45+3x-2x2 find and simplify 3P(a+6)-17. Discuss how each value shifts/scales the function

The following diagram shows the graph of y=f(x), for -4 ≤ x ≤ 5. ( Graph shows line starting at (-4, -3). It passes through the points (-2,0) and (0,1). It ends...

Example:p(t_ = 2t - 1 and q(t) = -t2 - 4t - 1. Find (q - p)(t) (q - p)(t) = q(t) - p(t) q(t) - p(t) "define" (-t2 - 4t - 1) - (2t - 1) "substitute" =(-t2...

f(x) = x + 4 g(x) = x - 3 for which value of x is (f⁄g)(x) undefined?

A question from trigonometry and functions... If "k tanx + tan(kx) = 0", prove: ((sin kx)^2)/(sinx)^2 = (k^2)÷((1+(k^2-1)(sinx)^2))

1. The function f(x) and g(x) are defined by f(x)=2^x and g(x)= log2(1-2x) a. Write down f^-1(x). b. (i). Find and simplify (f°g)(x) (ii) Find and simplify (f°g)^-1(x) c. (i) Write...